The Shift in the Role of Fathers in Childcare in Simpang Tiga, Pidie - Hanapi, Agustin; Husna, Nurul (Qanun: Jurnal Hukum Keluarga Islam, 2025)
The prevailing paradigm in society still positions child-rearing and education as primarily the mother's responsibility, while fathers are more often associated with the role of breadwinner. However, Islamic educational principles emphasize that both father and mother share equal responsibility in building a harmonious family and educating children. This study aims to analyze fathers' understanding of their roles in Islam, their involvement in early childhood care, and the development of children who receive paternal caregiving. The research employed a qualitative case study method, with data collection techniques including observation, interviews, field notes, and documentation. Data analysis was conducted through pattern matching, explanation building, and chronological analysis. The study involved three families with varying employment conditions of fathers and mothers. The findings reveal that optimal paternal involvement positively impacts child development, whereas in other families, fathers' participation in caregiving remains limited in both quality and quantity, with caregiving roles predominantly assisted by mothers and grandmothers. These findings highlight the importance of enhancing fathers' participation in childcare to foster balanced character development in children in accordance with Islamic educational principles.